Antimicrobial Resistance Pattern of Stenotrophomonas maltophilia Isolates from a Tertiary Care Setting in Rawalpindi, Pakistan - Usman Ali; Shahid Ahmad Abbasi; Fatima Kaleem; Tariq Butt; Sania Raza (Pasteur Institute of Iran, 2016)
Introduction: Stenotrophomonas maltophilia is intrinsically resistant to many antimicrobials. Like Pseudomonas spp., this bacterium has a remarkable ability to cause infections, particularly in the respiratory and urinary tracts. This study aims to determine the antimicrobial resistance pattern of S. maltophilia isolates collected from a tertiary care setting and frequency of multi, extensively and pandrug-resistant S. maltophilia. Methods: A cross-sectional study was carried out in Department of Microbiology, Fauji Foundation Hospital, Rawalpindi, Pakistan from January to June 2016. The isolates were identified as S. maltophilia using standard microbiological techniques, and the antimicrobial resistance was carried out using E-strip test against various antimicrobials. The data was analyzed and interpreted regarding frequencies and percentages. Results: Out of 90 isolates confirmed as S. maltophilia, pus (33.33%) and urine (24.44%) were the most common specimens from which this bacterium was isolated. Antimicrobial resistance pattern showed a high percentage of resistance to many antimicrobials with exception to aztreonam, minocycline, polymyxin B and colistin. Conclusion: Various S. maltophilia isolates from our set-up were resistant to antimicrobial agents used in the study. It is predicted that the infections caused by this bacterium shall be difficult to treat in the near future due to resistance to these antimicrobial agents. Though at this point no pandrug-resistant S. maltophilia is reported, the resistance pattern suggests that pandrug-resistant strains may appear shortly and when the time comes only newer antimicrobials can provide the answer.